STRATEGI KOMUNIKASI ANTI NARKOBA DALAM LITERASI MEDIA DI INDONESIA - sa, lisa; Utami, Atikah Dewi (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The State of Indonesia is currently facing a